The energy consumption characteristics of a new type of energy dissipating vibration-damping fastener - Yan Liu; Jiansen Zhu; Xianpu Yuan; Runhua Fan; Yuan Yuan (AIP Advances)
To address the issue of inadequate energy dissipation capacity in current vibration-damping fasteners, this study examined the impact of stiffness and damping factor of vibration-damping fasteners on the vibration attenuation rate of rails, based on the theoretical model of a periodic double-layer support system. An intrinsic manganese–copper (Mn–Cu) damping alloy model was established, and the parameters for the Prony analysis and PRF model were determined to accurately define the hyperelastic and linear viscoelastic properties of the damping alloy in the finite element simulation software. A new type of energy dissipating vibration-damping fastener (NEDF) was designed based on these criteria and practical operational conditions. Static and dynamic stiffness simulation calculations were performed to examine the vibration isolation ability of NEDF, which was then installed in a rail system to conduct hammering tests, aiming to investigate its energy dissipation characteristics. The results indicated that NEDF exhibited a high damping factor and maintained significant vibration isolation capacity, notably enhancing the vibration attenuation rate of the rails and improving energy dissipation capacity.